Impact of patient sex on selection for abdominal aortic aneurysm repair: a discrete choice experiment - Linda Sharples; Anna Louise Pouncey; Colin Bicknell; Mandy Ryan; Luis Enrique Loría-Rebolledo; Janet Powell (BMJ Open)
Objectives Women with an abdominal aortic aneurysm (AAA) are less likely to receive elective repair than men. This study explored the effect of patient sex and other attributes on vascular surgeons’ decision-making for infrarenal AAA repair.Design Discrete choice experiment.Setting Simulated environment using case scenarios with varying patient attributes.Participants Vascular surgeons.Interventions Surgical decision-making.Main outcome measures AAA repair versus no repair and endovascular versus open repair.Results 182 surgeons completed 2987 scenarios. When all other attributes were equal, a woman was more likely to be offered an AAA repair (marginal rate of substitution (MRS) 3.86 (95% CI 2.93, 4.79)), while very high anaesthetic risk (MRS −4.33 (95% CI –5.63, –3.03)) and hostile anatomy (MRS −3.28 (95% CI –4.55, –2.01)) were deterrents. Increasing age did not adversely affect the likelihood of offering repair to men but decreased the likelihood for women, which negated women’s selection advantage from the age of 83 years. Women were also more likely to be offered endovascular repair (MRS 2.57 (95% CI 1.30, 3.84)).Conclusions Patient sex alone did not account for real-world disparity observed in selection for surgery. Rather, being a woman was associated with a higher likelihood of being offered AAA repair but also a higher likelihood of being offered less invasive endovascular repair. Increased age decreased the likelihood of surgical selection for women but not men. Preference for less invasive repair, combined with inferior rates of anatomical suitability, and the comparably older age of women at the time of AAA repair selection may account for lower rates of repair for women observed.